Pengembang modul berbasis Problem Based Learning (PBL) terintegrasi literasi sains pada materi laju reaksi kimia - Sembiring, Hanna Grace; Sutiani, Ani (ARKA INSTITUTE, 2022)
This study aims to develop a problem-based learning (PBL) module integrated with scientific literacy on the reaction rate material. The type of research used is Research and Development (R&D). The subject of this study is a PBL-based module integrated with scientific literacy. The object of this study is the chemical reaction rate material. This study refers to the steps of Borg and Gall but is limited to 5 steps or stages. The steps begin with data and information collection, PBL-based module development planning, initial product development, initial field trials, and revision of trial results. The developed module is validated and tested. Meanwhile, to see the attractiveness of the module, a data collection method is carried out using a research instrument in the form of a questionnaire. The results of the study showed that the PBL-based module integrated with scientific literacy on the chemical reaction rate material was declared feasible after validation. And declared interesting after obtaining a very interesting category percentage. It can be concluded that the development of a problem-based learning (PBL) module integrated with scientific literacy on the reaction rate material has been successful and can be used in learning activities.